A small molecule targeting myoferlin exerts promising anti-tumor effects on breast cancer - Tao Zhang (Nature Portfolio, 2018)
Improved therapeutics are needed for treating breast cancer. Here they show the druggability of myoferlin with a small molecule inhibitor in breast cancer and demonstrate its anti-breast cancer effects in vitro and in vivo.